Opportunities for junior members at the ERS International Congress 2016. Issue 3 (September 2016) - Boots, Agnes; Flood, Emma; Skoczynski, Szymon
As the 2016 ERS International Congress in London is approaching, we would like to highlight that there will be various opportunities to get involved in the Junior Members Committee (JMC; soon to be renamed the Early Career Members Committee) during this meeting. Getting involved in the JMC does not require you to be well-known or established within your field, but instead to be engaged with the Society and the possibilities it provides for junior and early career members. You can become involved in the JMC by putting yourself forward for nomination at one of the forthcoming elections for this committee. Junior member activities at the ERS International Congress 2016 http://ow.ly/uNDZ302hwFK